2017
DOI: 10.21608/epx.2017.7008
|View full text |Cite
|
Sign up to set email alerts
|

University Students’ knowledge, attitudes, and practices towards the National Premarital Screening Program of Saudi Arabia

Abstract: Most Taif University students have a generally positive attitude and good intended practices toward PMS. However, targeted educational programs about the importance of PMS are strongly recommended to eliminate all factors that may affect the success of the PMS program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 14 publications
2
7
0
Order By: Relevance
“…For instance, one study has reported that unmarried female university students had inadequate knowledge: less than one-third of participants knew which disorders are tested for. 18 , 19 Similar findings have been reported in Jeddah: participants from governmental outpatient clinics have been found to have low knowledge of premarital screening. 20 Similarly, in a study by Al-Shroby et al.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…For instance, one study has reported that unmarried female university students had inadequate knowledge: less than one-third of participants knew which disorders are tested for. 18 , 19 Similar findings have been reported in Jeddah: participants from governmental outpatient clinics have been found to have low knowledge of premarital screening. 20 Similarly, in a study by Al-Shroby et al.…”
Section: Discussionsupporting
confidence: 66%
“…Most respondents were willing to change their marriage decisions in the event of incompatibility, a finding in line with those from other studies in the literature. 19 , 22 Notably, another program called the National Newborn Screening Program aims to screen newborns across the Kingdom to achieve early detection of hereditary diseases that would cause serious health complications. 28 , 29 However, having a compulsory preventive program that screens for genetic and hereditary diseases in individuals who intend to marry is essential to decrease the transmission of these diseases, particularly in cultures with a high rate of consanguineous marriages, which increase the frequency of congenital diseases affecting the population.…”
Section: Discussionmentioning
confidence: 99%
“…There is no conflict of interest and no financial support for any of the authors. agreed that hereditary diseases had psychological and economic effects on the families (88.7%, 79.8% respectively) [14].In the current study, the majority (85.2%) of respondents disagreed that the PMSGC was against their religious/ cultural beliefs. In addition, almost all (94.8%) of the studied sample agreed that religious leaders should deliver messages on the importance of the PMCS and genetic counselling, which is a good attitude.…”
Section: Reliability (Alpha Cronbach) Validitymentioning
confidence: 49%
“… 5–8 Each of these studies was conducted in the United States, except for Melaibari et al's study, which investigated views of young adults in Saudi Arabia on the national premarital screening program of the country. 9 Findings were similar across the board, with studies indicating a general lack of knowledge about reproductive options and sickle cell inheritance, and confusion about adequacy of resources for this information. The qualitative studies we identified follow a similar trend—exploring attitudes, beliefs, and reproductive decision-making of individuals with SCD or SCT.…”
Section: Introductionmentioning
confidence: 68%